The clinico-pathological findings of surgically treated goiter
Background: Goiter is one of the most common conditions that affect people’s at different age groups with its effect on the metabolic status of the body through the hyper&/hypo functioning gland that may needs surgical resection. This prospective study had been conducted on 100 patient (85 females&15 males